2015
DOI: 10.1097/aap.0000000000000194
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study of Epidural Blood Patch Use for Spontaneous Intracranial Hypotension

Abstract: Our study suggests that the response to the EBP is related to the severity of symptoms but not to the number and locations of cisternographic CSF leakages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…In our previous study, we found that the response to autologous EBP was related to the severity of symptoms but not to the number and location of CSF leakages. 21 One of the limitations of our previous study was that we only dealt with the number of leakage sites without any quantitative analysis of the amount of leakage because there are no proper tools to measure this. 21 We, therefore, decided to use 6 surrogate markers of the quantitative evaluation of leakage based on previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we found that the response to autologous EBP was related to the severity of symptoms but not to the number and location of CSF leakages. 21 One of the limitations of our previous study was that we only dealt with the number of leakage sites without any quantitative analysis of the amount of leakage because there are no proper tools to measure this. 21 We, therefore, decided to use 6 surrogate markers of the quantitative evaluation of leakage based on previous studies.…”
Section: Discussionmentioning
confidence: 99%
“… 21 One of the limitations of our previous study was that we only dealt with the number of leakage sites without any quantitative analysis of the amount of leakage because there are no proper tools to measure this. 21 We, therefore, decided to use 6 surrogate markers of the quantitative evaluation of leakage based on previous studies. 1 , 2 , 22 The first marker was derived from the study of Morioka et al 1 who evaluated four indirect findings of CSF leakage on RI cisternography, such as the early visualization of bladder activity, no visualization of activity over the brain convexities, rapid disappearance of spinal activity, and abnormal visualization of the root sleeves.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, many patients require more than one EBP or other treatments such as epidural saline/ fibrin glue infusion and IT fluid infusion. [22][23][24][25][26] In the present study we aimed to elucidate predictors of a positive response to an EBP based on clinical characteristics, subjective symptoms, and neuroradiological signs, which revealed that these predictors were age, interval from the onset to EBP application, rate of RI remaining after 24 hours, epidural CSF collection in MRI, epidural CFS leak in RI cisternography, orthostatic headache, nuchal pain, photophobia, and nausea. Our finding that being younger and having a shorter interval from the onset to EBP application were significant predictors suggests that spinal CSF leakage should be treated early.…”
Section: Jcnmentioning
confidence: 99%
“…2). Nicht selten weisen die Patienten 2 oder auch mehrere Liquorlecks auf [1,11]. Neben dem primären Einriss der Dura sind es häu-fig zystisch erweiterte Wurzeltaschen, die sich als Locus minoris resistentiae erweisen und zum Liquorleck führen.…”
Section: Diagnostik Des Liquorunterdrucksyndromsunclassified
“…Je nach Compliance des Patienten können diese jedoch in einer einzelnen Sitzung appliziert werden. In einer aktuellen Studie zur Wirksamkeit des "blood patch" ergab sich als Ergebnis, dass die insgesamt benötigte Anzahl an "blood patches" nicht mit der Anzahl der Liquorleckagen korreliert, hierfür aber signifikant mit dem ursprünglichen Schweregrad der Beschwerden vor Therapiebeginn [11].…”
Section: Ergebnisseunclassified